2020
DOI: 10.1097/iop.0000000000001876
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Fibrotic Contraction by Sirolimus (Rapamycin) in an Ex Vivo Model of Thyroid Eye Disease

Abstract: Background: Thyroid eye disease (TED) is characterized by orbital inflammation and complicated by extraocular muscle fibrosis. Treatment with rapamycin/sirolimus has been reported to improve ocular motility and disease manifestations in TED. Whether this resulted from a primary antifibrotic effect on fibroblasts or was secondary to immune-suppression is unclear. Methods: In vitro contractility studies of primary orbital fibroblasts. Cells from patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 46 publications
0
7
0
2
Order By: Relevance
“…Moreover, in vitro studies showed that rapamycin can directly suppress fibroblasts and preadipocytes, leading to reductions in fibrosis and adipogenesis, respectively (29,30). Thus, rapamycin is a plausible therapeutic agent for the management of GO and should be investigated in randomized clinical trials (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in vitro studies showed that rapamycin can directly suppress fibroblasts and preadipocytes, leading to reductions in fibrosis and adipogenesis, respectively (29,30). Thus, rapamycin is a plausible therapeutic agent for the management of GO and should be investigated in randomized clinical trials (31).…”
Section: Discussionmentioning
confidence: 99%
“…The rapid and effective suppression of GO-pathogenic CD4 + CTLs makes it one of the main mechanisms underlying the remarkable efficacy of rapamycin in GO, although Th1 cells, Th17 cells, and T regs are also reportedly potential targets ( 28 ). Moreover, in vitro studies showed that rapamycin can directly suppress fibroblasts and preadipocytes, leading to reductions in fibrosis and adipogenesis, respectively ( 29 , 30 ). Thus, rapamycin is a plausible therapeutic agent for the management of GO and should be investigated in randomized clinical trials ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have shown that sirolimus-mediated inhibition of mTORC1 is followed by a block in adipogenesis in preadipocytes and fibroblasts from GO patients. In addition, by blocking the FRAP/mTOR signaling pathway, sirolimus reduces the synthesis of IL-16 promoted by circulating IgGs in orbital fibroblasts [18][19][20]. IL-16, together with the chemokine RANTES, represents one of the main mediators of "trafficking" of CD4-positive T lymphocytes in GO [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Given the molecular mechanisms of action of sirolimus, as teprotumumab, the drug may block IGF-1 signaling as well as other pathways involved in migration, proliferation, differentiation and cell activation, resulting in similar clinical effects, as we observed here. Furthermore, recent in vitro studies have shown that sirolimus affects tissue remodelling also by negatively regulating fibroblast migration and fibroblast transition into myofibroblasts, therefore reducing the production of collagen and extracellular matrix [20,23]. The anti-fibrotic effect of sirolimus has also been demonstrated in vivo in a murine model [24][25][26], and it has been proposed as one of the possible explanations for the efficacy of this drug in the two patients with GO reported previously [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…V.a. die Fibrose wird dabei adressiert [107].In einer Fall-Kontroll-Studie erhielten Patienten Sirolimus 2 mg oral am ersten Tag, gefolgt von 0,5 mg/Tag für 12 Wochen -Therapieeffekte wurden mit einer konsekutiven Kohorte verglichen, die kumulativ 4,5g IVGC erhielt. Es zeigte sich ein stärkerer Therapieeffekt für Sirolimus 86% versus 26% [73].…”
Section: Cyclosporin (Csa)unclassified